Investigating the role of iASPP in cutaneous disorders - Dedeić, Z (2014)
Desmosomes are intercellular junctions that anchor intermediate filaments to the sites of intercellular contacts. They are critical for maintaining the integrity of tissues that experience constant mechanical and structural stresses, like the skin and heart. Perturbation of desmosomal adhesion can lead to devastating epidermal and myocardial diseases. However, little is known about the regulators of desmosomes and the role of desmosomes in cell signalling events. Recent work has suggested that iASPP, an inhibitor of the p53 family of proteins, localises at the intercalated discs where desmosomes reside. However, its role at the desmosomes has remained elusive. Thus, in this thesis, it was investigated whether iASPP is a dual function protein that links desmosome adhesion to gene expression and if desmosome-related diseases develop in the absence of iASPP. iASPP was found to be a novel regulator of desmosomes, co-localising with them by physically interacting with the desmosomal components desmoplakin and K5 intermediate filaments. Loss of iASPP resulted in increased phosphorylation and solubilisation of desmoplakin, leading to the formation of K5 aggregates. This culminated in disrupted intercellular adhesion and enhanced cellular migration. Consistent with the role of iASPP in the maintenance of desmosomal adhesion integrity, focal palmoplantar keratoderma was observed in iASPP-deficient mice — a disorder often associated with desmosome dysfunction. This was accompanied by disrupted intracellular signalling, as exemplified by the disrupted expression of differentiation markers; an increase in the thickness of cell layers expressing differentiation marker K1 was noted, and K5 and K6 cells were ectopically expressed throughout the diseased palmoplantar epidermis. Impaired intercellular adhesion and migration had consequences for wound healing, as iASPP-deficient mice exhibited delayed wound closure. Furthermore, defects in eyelid closure in iASPP-deficient mice were found to be due to increased apoptosis. The localisation of apoptotic cells at the leading edge of the eyelid epidermis implied that apoptosis might have occurred due to a loss of cell-matrix or cell-cell contact, i.e. anoikis. Taken together, these results suggest that iASPP is involved in pathological (palmoplantar keratoderma), physiological (wound healing) and developmental processes (embryonic eyelid closure) through its regulation of desmosomes and their dynamics. Therefore, iASPP represents a new candidate gene in cutaneous disorders and could be implicated in a variety of epidermal and myocardial diseases.